Compositional control of radionuclide retention in hollandite‐based ceramic waste forms for Cs‐immobilization. Issue 7 (31st December 2018) - Zhao, Mingyang; Xu, Yun; Shuller‐Nickles, Lindsay; Amoroso, Jake; Frenkel, Anatoly I.; Li, Yuanyuan; Gong, Weiping; Lilova, Kristina; Navrotsky, Alexandra; Brinkman, Kyle S.
Abstract: Hollandite materials, as a class of crystalline nuclear waste forms, are promising candidates for the immobilization of radioactive elements, such as Cs, Ba, as well as a variety of lanthanide and transition‐metal fission products. In this study, three Ga‐doped titanate hollandite‐type phases, Ba1.33 Ga2.67 Ti5.33 O16, Ba0.667 Cs0.667 Ga2 Ti6 O16, and Cs1.33 Ga1.33 Ti6.67 O16, were synthesized using a solid‐state reaction route. All synthesized phases adopted a single phase tetragonal structure, as determined by powder X‐ray diffraction (XRD), and elemental analysis confirmed the measured stoichiometries were close to targeted compositions. Extended X‐ray absorption fine structure spectroscopy (EXAFS) was used to determine the local structural features for the framework of octahedrally coordinated cations. EXAFS data indicated that Cs1.33 Ga1.33 Ti6.67 O16 possessed the most disordered local structure centered around the Ga dopant. The enthalpies of formation of all three hollandite phases measured using high‐temperature oxide melt solution calorimetry were found to be negative, indicating enthalpies of formation of these hollandites from oxides are thermodynamically stable with respect to their constituent oxides. Furthermore, the formation enthalpies were more negative and hence more favorable with increased Cs content. Finally, aqueous leaching tests revealed that high Cs content hollandite phases exhibited greater Cs retention as compared to low Cs content hollandite. While preliminary in nature, this work draws attention to the links between the capacity for radionuclide retention, atomistic level structural features and bulk thermodynamic properties of materials.